EFFECT INFLUENCER, P2P REPUTATION AND RISK PERCEPTION TOWARDS INVESTMENT DECISIONS OF MILLENIAL IN P2P LENDING: FINANCIAL LITERACY AS A MEDIATION VARIABLE - Felicia Priscilla; Mustaruddin Saleh (Universitas Riau Kepulauan, 2023)
P2P lending is a fintech innovation that makes it easier to apply for credit than banks. Many investors were tricked and faced other losses for their investment decisions in P2P lending. Therefore, this study examines the impact of Influencer, P2P reputation, and Risk Perception on Investment decisions of Millennials in P2P Lending with Financial Literacy as a mediation variable. The research conducted is focused on millennial investors. With the purposive sampling technique, there are 50 research samples obtained. The research sample is compiled by distributing the questionnaire online through Google Form. The data analysis used SmartPLS 3.0 software, divided into descriptive analysis, path analysis, and partial test (T-test). Results show that influencer significantly affects investment decision and is non-significant to financial literacy. Meanwhile, P2P reputation and risk perception are significant for financial literacy yet insignificant for investment decision. Financial literacy is not significant to investment decision and unable to mediate influencer, P2P reputation, and risk perception to investment decision. Keywords: P2P lending, Influencer, Millennial, P2P Platform, Risk Perception, Financial Literacy.